Is management of spontaneous intracranial extradural hematoma in chronic renal failure is different with traumatic extradural hematoma -Case report and review of literature - Rajput, Dinesh K.; Kamboj, Rohit; Srivastav, Arun K; Kaval, Priyanka; Kumar, Raj (Indian Journal of Neurotrauma, 2010)
Intracranial extradural hematoma is commonly associated with head trauma. Spontaneous EDH is a rare entity and associated with various co morbid conditions. Chronic renal failure (CRF) is one of them. In case of CRF, spontaneous EDH has been reported in those patients who were either on hemodialysis or had long history of CRF. We report a case of concurrently asymptomatic chronic renal failure that developed spontaneous EDH with neurological deficits and during investigation, diagnosed to have acute on chronic renal failure. Investigation and management is discussed in the report.
Keywords: Spontaneous; Extradural hematoma; chronic renal disease